THE INFLUENCE OF Aloe vera AND XENOGRAFT (XCB) TOWARD OF BONE MORPHO PROTEIN 2 ( BMP2) EXPRESSION AND AMOUNT OF OSTEOBLAST OF ALVEOLAR BONE INDUCED INTO TOOTH EXTRACTION SOCKETS (Cavia cobaya) - Utari Kresnoadi; Retno Pudji Rahayu (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2014)
Tooth extraction can cause inflammation leading to alveolar ridge resorption. In addition, prominent ridge has crucial role for making denture successfully. Thus, socket preservation is needed to prevent greater alveolar ridge resorption. An innovative material, a combination of Aloe vera and xenograft (XCB), is then considered as a biogenic stimulator that can reduce inflammation, as a result, the growth of alveolar bone is expected to be improved. This research is aimed to prove whether the mixture of Aloe vera and xenograft can stimulate BMP2 and increase osteoblasts. Forty-eight Cavia cobaya animals were divided into eight groups each of which consisted of six animals. The mandibular incisors of those Cavia cobaya animals were then extracted and filled with PEG as Group Control, XCB as Group XCB, Aloe vera as Group Aloe vera, and a combination of Aloe vera +XCB as Group Aloe vera +XCB. Next, the first four groups were sacrificed seven days after extraction, and the second four groups were sacrificed 30 days after extrac-tion. And then, immunohistochemical and histopathology examinations were conducted to examine BMP2 expression and osteoblasts. Based on the re-sult known that the mixture of Aloe vera and xenograft can increase BMP2 expression and amount of osteoblasts. It can be concluded that the mixture of Aloe vera and xenograft can increase BMP2 expression and amount of osteoblast cel . It can be used as an alternative material to increase the growth of alveolar bone after extraction.